Perceptions, Legislation, and Management of Cultural Heritage in Ethiopia. Issue 1 (3rd March 2016) - Nair, Vijayakumar Somasekharan
Abstract: The present article discusses perceptions of cultural heritage and the development of heritage management in Ethiopia against the background of various pieces of legislation. Compared to many colonized countries of sub-Saharan Africa, the enactment of laws for the protection and preservation of cultural heritage is a recent phenomenon in Ethiopia. Even though archaeological research in Ethiopia dates back to the mid-nineteenth century, there have been no formal heritage laws or scientific restoration programs until 1966. However, living heritage, which is economically and spiritually beneficial to the local communities, has been protected and preserved with TMSs in communities such as Yeha, Konso, and Lalibela. Unlike Western management systems that emphasize the authenticity and integrity of physical features, the TMSs of Ethiopia have focused on the ideals and thoughts of the agencies that produce the cultural heritage. It had its own implications, to say, while retaining the ideological aspects, most built heritages in Ethiopia have been subjected to considerable physical interventions. Such physical interventions have disregarded structural authenticity and integrity of the monuments. Due to foreign invasions, continuous civil conflicts, and sporadic famines in the past, attention to cultural heritage and the implementation of heritage legislation has been negligent. However, Ethiopia has witnessed growing interest in the conservation and preservation of its heritage—cultural and natural; tangible and intangible—during the last twenty years. With the support of international collaborators, the Ethiopian government has initiated several measures to protect its heritage assets.